Packaging Design (Secondary) of Woven Bamboo and Its Effect on Jaje Gambir Characteristics - Andrean, Roqi Asrori; Sucipta, Nyoman; Kencana, Pande Ketut Diah (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The purpose of this study was to determine the shelf life of Jaje Gambir are packed with packaging made of woven bamboo-based. The study also aimed to design or designing packaging for Jaje Gambir, which serve as the base material is a woven bamboo. The experiment was conducted using a completely randomized design (CRD). In this study, the packaging has been created and woven into shape at the time of trial run given that treatment with the coating, plating treatment is performed is coated with plastic wrap. This type of treatment given in this study there are four kinds, namely, P1 (without coating), P2 (inner packaging plastic coated, outer uncoated), P3 (inner packaging is not coated with plastic, outer plastic coated) and P4 ( packaging plastic coated on the outside and inside). This study in addition to determine the shelf life of Jaje Gambir also to determine public perceptions of packaging designs that have been made, to test it conducted a survey and assessment of the public perception of the packaging design is created. The results showed a shelf life of Jaje Gambir is for 2 weeks, the product is still in a decent state only until the second week. In the next week the quality and the quality of products has decreased and is not suitable for consumption, the texture of the product has become harder and discoloration of Jaje Gambir become yellowish due to the emergence of the fungus on Jaje Gambir. The results of the public perception survey showed the average people agree with the statement contained in the questionnaire and likes to design packaging made of woven bamboo.